2019
DOI: 10.1515/secm-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PVC/MWCNTs Nanocomposite: Solvent Blend

Abstract: Polyvinyl Vinyl Chloride (PVC) multiwall carbon nanotubes (MWCNTs) nanocomposite flexible films were prepared using the solvent blend technique. Chloroform (CHCl3) and tetrahydrofuran ((CH2)4O) were used as solvents for MWCNTs and PVC, respectively. The effect of the solvents’ blend on electrical, optical and thermal properties of PVC/MWCNTs were investigated. The results of the Raman spectrum showed that all the characteristic bands of PVC polymer have a slight shift due to addition of MWCNTs. Electrical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…An important problem in the synthesis scheme of PCCCM considered above is to ensure close interaction of the modifying additive nanoparticles with the initial polyvinyl chloride molecules (or aggregates of molecules). This problem is of interest, per se; it is considered in many studies where PVC modification by carbon NC is used to render antistatic or shielding properties to NC/PVC composite materials [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], to improve thermal or electrophysical properties [ 39 , 40 , 41 , 42 , 43 , 44 ], and to apply such materials in energy storage devices [ 41 , 42 ], chemical sensors [ 41 , 42 ] and microelectronics [ 39 , 44 ]. A uniform distribution of carbon nanoparticles in PVC melt or its solutions in organic solvents is obtained using ultrasonic treatment [ 33 , 40 , 41 , 42 , 44 , 45 ], preliminary surface functionalization of the modifying carbon nanoparticles [ 46 , 47 , 48 ], surfactant additives [ 49 , 50 ], and mechanical mixing in a dry form in special-purpose mills [ 35 , 39 , 42 , 43 ] or extruders [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important problem in the synthesis scheme of PCCCM considered above is to ensure close interaction of the modifying additive nanoparticles with the initial polyvinyl chloride molecules (or aggregates of molecules). This problem is of interest, per se; it is considered in many studies where PVC modification by carbon NC is used to render antistatic or shielding properties to NC/PVC composite materials [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], to improve thermal or electrophysical properties [ 39 , 40 , 41 , 42 , 43 , 44 ], and to apply such materials in energy storage devices [ 41 , 42 ], chemical sensors [ 41 , 42 ] and microelectronics [ 39 , 44 ]. A uniform distribution of carbon nanoparticles in PVC melt or its solutions in organic solvents is obtained using ultrasonic treatment [ 33 , 40 , 41 , 42 , 44 , 45 ], preliminary surface functionalization of the modifying carbon nanoparticles [ 46 , 47 , 48 ], surfactant additives [ 49 , 50 ], and mechanical mixing in a dry form in special-purpose mills [ 35 , 39 , 42 , 43 ] or extruders [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…This problem is of interest, per se; it is considered in many studies where PVC modification by carbon NC is used to render antistatic or shielding properties to NC/PVC composite materials [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], to improve thermal or electrophysical properties [ 39 , 40 , 41 , 42 , 43 , 44 ], and to apply such materials in energy storage devices [ 41 , 42 ], chemical sensors [ 41 , 42 ] and microelectronics [ 39 , 44 ]. A uniform distribution of carbon nanoparticles in PVC melt or its solutions in organic solvents is obtained using ultrasonic treatment [ 33 , 40 , 41 , 42 , 44 , 45 ], preliminary surface functionalization of the modifying carbon nanoparticles [ 46 , 47 , 48 ], surfactant additives [ 49 , 50 ], and mechanical mixing in a dry form in special-purpose mills [ 35 , 39 , 42 , 43 ] or extruders [ 33 , 34 ]. The analysis of available publications showed that the most efficient contact of the modifying additive with chloropolymer molecules (or aggregates of molecules) during the synthesis of such polymer–carbon nanocomposites is achieved in an ultrasonically treated liquid medium [ 33 , 40 , 41 , 42 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…We note a difference in the appearance of the two spectra with the appearance of additive peaks on the spectrum of the doped PVC, so we can say that the doping is successful. The lines located at 360.472, 356.671, and 696.756 cm − 1 are common and are due to the PVC, Which is attributed to the vibration of the elongation of the C-Cl bond [32]. While the additive lines, due to ZnO crystallites, are located between 315 to 322 cm − 1 and among 422 to 439 cm − 1 .…”
Section: Raman Spectroscopy Analysismentioning
confidence: 96%
“…They also reported that nanocellulose is generally considered as potential and excellent reinforcing ller for manufacturing nanocomposites as they are renewable, possess lightweight and is cost effective. Naim et al (2020) investigated and reported on the polyvinyl chloride (PVC) multiwall carbon nanotubes (MWCNTs) nanocomposite for many industrial applications such as energy storage, chemical sensors and electronics etc. Poly(vinyl chloride) (PVC) was one of the rst polymers to be used in food packaging applications due to its wide acceptance for use in the preservation of foods.…”
Section: Introductionmentioning
confidence: 99%